Berührungen: Bewegung, Relation und Affekt im zeitgenössischen Tanz - Egert, Gerko (transcript, 2016)
Lifting, grazing, holding, pushing – dance involves diverse forms of touching. Departing from the assumption that touching is more than merely the contact of two bodies, Gerko Egert sketches out a conception of touching as the complex interplay of movements, experiences and affects. In detailed analyses of contemporary dance performances and the critical confrontation with concepts of rhythm, event and arrangement, new perspectives on the body, perception and movement are developed. This book does not just open up the question of touching for dance studies, but also provides an equally pivotal contribution to a process-oriented theory of touching.